Peningkatan Motivasi Dan Hasil Belajar Siswa Pada Materi Koordinat Kartesius Melalui Pembelajaran Discovery Learning Berbantuan Powerpoint Interaktif - Maiten, Mery Kristin; Nenohai, Juliana M. H.; Blegur, Irna K. S. (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2024)
The underlying issue addressed in this research is the low motivation and learning outcomes of students. This is attributed to the conventional teaching model, which is teacher-centered and the use of media that tends to make students passive and uninterested in the learning process. The aim of this study is to describe the improvement in motivation and learning outcomes of 8th-grade students at Catholic Junior High School Muder Teresa on cartesian coordinate material through discovery learning assisted by interactive powerpoint. The research method used is Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting og 4 stages, namely Planning, Impelemtation, Observation and reflection. Data collection techniques used include observation, interviews, questionnaires tests and documentation. Furthermore, the data were analyzed descriptively. The research result showed in the initial condition average motivation score of students at 53,86. Increasedto 70.5 in first cycle, and 79.64 in the second cycle. While the percentage of students who complated was 57.14% in the first cycle and second cyclewas 89.29%. Thus it can be concluded that the discovery learning model assisted by interactive powerpoint can improve the motivation and learning outcomes of 8th-grade students at Catholic Junior High School Muder Teresa on cartesian coordinate material. Keywords: Discovery Learning, Interactive Powerpoint, Learning Outcomes and Motivation